Analisis Rasch model Indonesia Problematic Internet Use Scale (IPIUS) - Natanael, Yonathan (Persona:Jurnal Psikologi Indonesia, 2021)
Abstract Indonesia Problematic Internet Use Scale (IPIUS) consists of six dimensions, namely a preference for online social interaction, escaping, negative outcomes, compulsive internet use, cognitive preoccupation, and emotional reactivity. University students in the covid-19 pandemic are constantly learning to use the internet that causes compulsive internet use. This study explores IPIUS using analysis technique rating scale model, especially the compulsive internet use dimension which consists of ten items. The quantitative research method is survey research using an online questionnaire. Participants in the research were 395 university students who do lectures online. The sampling technique used to obtain participants was convenience sampling. The results showed nine-item compulsive internet use dimension is good quality, unidimensional, and item reliability was better than previous research using confirmatory factor analysis. IPIUS is a stable instrument to measure problematic internet use for university students in Indonesia.   Keywords: compulsive internet use; covid-19; problematic internet use; rating scale model, university students Abstrak Indonesia Problematic Internet Use Scale (IPIUS) terdiri dari enam dimensi, yaitu: preference for online social interaction, escaping, negative outcome, compulsive internet use, cognitive preoccupation, dan emotional reactivity. Mahasiswa di era pandemic covid-19 secara terus-menerus melakukan pembelajaran daring yang mengakibatkan menjadi compulsive internet use. Penelitian ini bertujuan mengekplorasi IPIUS dengan menggunakan teknik analisis rating scale model, khususnya dimensi compulsive internet use yang terdiri dari sepuluh item. Metode penelitian kuantitatif yang digunakan berjenis survey research menggunakan kuesioner online. Partisipan penelitian sebanyak 395 mahasiswa yang melakukan kuliah secara daring. Teknik sampling yang digunakan untuk mendapatkan partisipan adalah teknik convenience sampling. Hasil penelitian menunjukan sembilan item pada dimensi compulsive internet use merupakan item yang berkualitas baik, bersifat unidimensi, dan nilai reliabilitas item yang dihasilkan lebih baik dibandingkan penelitian sebelumnya yang menggunakan confirmatory factor analysis. IPIUS merupakan instrumen yang cocok mengukur problematic internet use pada mahasiswa di Indonesia.      Kata kunci: compulsive internet use; covid-19; problematic internet use; rating scale model mahasiswa